PENINGKATAN DAYA SAING PRODUK SINGKONG KRISPI MOTEKAR JAYA MELALUI DIGITAL MARKETING DI DESA SUNALARI KECAMATAN CIKIJING KABUPATEN MAJALENGKA - Uyu Wahyudin; Cecep Nana Nasuha; Dudi Komaludin; Jaenal Gopur Asmanul Salam (Jurnal Pengabdian Kepada Masyarakat, 2024)
sub-district. This village has a lot of potential and should be used to present the MSME products that they make. Cassava Crispy Motekar Jaya, a cassava chip snack, is one of the MSME products created in Sunalari village. One of the challenges that MSMEs in Motekar Jaya confront is a lack of information technology competence, particularly in the use of digital media such as social media. Because MSMEs' ability to advertise their products is still limited, their products are not effectively digested or understood by the population in general. This community service activity aims to help bring MSME products to a larger market through online marketing / digital marketing. To address issues in this service, the idea is to provide counseling and training to MSME players who are partners.